Flood risk management and governance: A bibliometric review of the literature. Issue 2 (25th February 2022) - Dordi, Truzaar; Henstra, Daniel; Thistlethwaite, Jason
Abstract: The study of flood management has experienced a paradigmatic shift over the past two decades. Particularly notable are the embracement of flood risk management (FRM) and comparative analysis of flood risk governance (FRG), meaning the complex institutional arrangements that shape the behavior of state and societal actors concerning FRM. Thousands of publications have addressed these themes, and this field of study is ripe for a systematic analysis that consolidates and structures this rapidly evolving literature. This study employed a bibliometric methodology to analyze the metadata (including authorship, keywords, abstracts, and citations) of 3059 such publications. The results reveal that both FRM and FRG scholarship have expanded over the past two decades; the United Kingdom and the Netherlands are the most prominent countries of origin, a small number of prolific authors stands out as major contributors, and a relatively small number of journals dominate as publication venues. The text mining results reveal that the bodies of FRM and FRG scholarship are highly correlated but yet differ in core subject matter, as demonstrated by the unique keywords found in the analysis. The findings are useful for researchers seeking relevant clusters for study and therefore offers reference value for future research and practice.